1998
DOI: 10.1007/978-1-4757-2909-2
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Child Abuse Research and Treatment

Abstract: A Continuation Order Plan is available for this series. A continuation order will bring delivery of each new volume immediately upon publication. Volumes are billed only upon actual sh ipment. For further information please contact the pub lisher. LIbrary of Congress CatalogIng-In-PublIcatIon Data Handbook of ch Ild abuse research and treatment I ed Ited by John R. Lutzker . p . cm . --(Issues In clInIcal chIld ps ychology) Includes bIblIographIcal references and Index. 1. Ch I l d abuse--Psychologlca l aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 476 publications
0
6
0
Order By: Relevance
“…Siblings can experience a wide variety of problems including internalizing and externalizing symptoms (Pogue & Hansen, 2016) and may engage in negative behaviors toward the victim and non-offending caregiver (e.g., anger, not believing the victim). The severity of the abuse, length of time that the abuse occurred, perpetrator's relationship to the family, location of the abuse, the sibling's age, disposition when faced with uncertainty and stress, and the closeness of the victim's relationship to the sibling may influence the sibling's emotional and behavioral response (Baker et al, 2001;Hill, 2003;Swenson & Hanson, 1998).…”
Section: Siblings' Emotional and Behavioral Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…Siblings can experience a wide variety of problems including internalizing and externalizing symptoms (Pogue & Hansen, 2016) and may engage in negative behaviors toward the victim and non-offending caregiver (e.g., anger, not believing the victim). The severity of the abuse, length of time that the abuse occurred, perpetrator's relationship to the family, location of the abuse, the sibling's age, disposition when faced with uncertainty and stress, and the closeness of the victim's relationship to the sibling may influence the sibling's emotional and behavioral response (Baker et al, 2001;Hill, 2003;Swenson & Hanson, 1998).…”
Section: Siblings' Emotional and Behavioral Responsesmentioning
confidence: 99%
“…Research has found that intrafamilial abuse is associated with greater negative outcomes for victims (Murray et al, 2014;Stroebel et al, 2012;Swenson & Hanson, 1998). The literature has suggested that intrafamilial CSA tends to occur in families that are more disorganized and chaotic, have increased psychosocial stressors, and are more socially isolated compared to families without CSA and to families with extrafamilial offenders (Levitt et al, 1991;Ray, Jackson, & Townsley, 1991;Seto et al, 2015;Swenson & Hanson, 1998;Wright, 1991). Many of these same factors, including parent-child relationship conflict, divorce, and low family cohesion, are associated with increased likelihood of depression (Lewinsohn et al, 1994).…”
Section: Family Stress and Disruptionmentioning
confidence: 99%
See 3 more Smart Citations